2008
DOI: 10.1002/ijc.23958
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and frequency of circulating t(14;18)‐MBR translocation carrying cells in healthy individuals

Abstract: The t(14;18) translocation is a common genetic aberration that can be seen as an early step in pathogenesis of follicular lymphoma (FL). The significance of low level circulating t(14;18)-positive cells in healthy individuals as clonal lymphoma precursors or indicators of risk is still unclear. We determined the age dependent prevalence and frequency of BCL2/IgH rearrangements in 715 healthy individuals ranging from newborns to octo- and nonagenarians. These results were compared with number of circulating t(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 25 publications
6
57
0
2
Order By: Relevance
“…In our study population, we detected that this rearrangement was present in 37.8 % of our population, similar to that described in other studies performed in healthy individuals (40-60 %) (Nambiar and Raghavan 2012). Moreover, the frequency of the translocation increased with the age of individuals (30.9 vs 46.2 %), results which were also in line with previous studies Liu et al 1994;Nambiar and Raghavan 2010;Schüler et al 2009). The chromosome translocation BCR-ABL or t(9;22) involving the major region of BCR is found in patients with chronic myeloid leukemia (CML) and adult acute lymphoblastic leukemia (Zhen and Wang 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In our study population, we detected that this rearrangement was present in 37.8 % of our population, similar to that described in other studies performed in healthy individuals (40-60 %) (Nambiar and Raghavan 2012). Moreover, the frequency of the translocation increased with the age of individuals (30.9 vs 46.2 %), results which were also in line with previous studies Liu et al 1994;Nambiar and Raghavan 2010;Schüler et al 2009). The chromosome translocation BCR-ABL or t(9;22) involving the major region of BCR is found in patients with chronic myeloid leukemia (CML) and adult acute lymphoblastic leukemia (Zhen and Wang 2013).…”
Section: Discussionsupporting
confidence: 92%
“…20 This concept is also consistent with the observation that up to 66% of healthy individuals over the age of ten years have circulating cells with BCL2 translocations, and with the belief that these cells already have many FL-like features and colonize the GC niche. [21][22][23][24][25][26][27] Other non-FL/DLBCL B-cell, T-cell and classical Hodgkin type lymphomas have also been reported in 15-31% of patients with FLBUS. However, whether these bear any relationship to the FLBUS, reflect an increased propensity to develop lymphoma due to genetic or environmental factors, or simply result from the overt neoplasm leading to a tissue biopsy are all unknown.…”
Section: Discussionmentioning
confidence: 99%
“…2 A screening of healthy individuals indicated that t(14;18)(q32;q21)-positive B cells are detectable in the peripheral blood starting from the age of 10 years. 22 Thus, positive polymerase chain reaction results suggestive of a t(14;18)(q32;q21) in pediatric patients should be validated by an in situ technique, such as FISH, to prove that the translocation is a feature of the lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%